2009
DOI: 10.1016/j.ejpain.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with momentary pain measurement using electronic diaries: A systematic review

Abstract: Electronic diaries are increasingly used to assess daily pain in many different forms and populations. This systematic review aims to survey the characteristics of studies using electronic pain diaries and to examine how these characteristics affect compliance. A literature search of 11 electronic databases was conducted. Studies were evaluated on the basis of predetermined inclusion criteria by two independent reviewers. Study characteristics were grouped into four categories: general, population, electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
163
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 65 publications
(35 reference statements)
24
163
5
1
Order By: Relevance
“…for them to text details of the type, frequency and duration of their physical activity at the time of engagement). Electronic diaries may be considered in future studies since they have demonstrated higher rates of compliance (83-94%) [38,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…for them to text details of the type, frequency and duration of their physical activity at the time of engagement). Electronic diaries may be considered in future studies since they have demonstrated higher rates of compliance (83-94%) [38,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of studies on pain that utilized electronic DDA implemented via smartphones, personal digital devices, and tablets reported: (a) high compliance rates overall among subjects aged 18 to 83 [55] and (b) rates of compliance significantly increased as the subject's age increased. In a recent study that implemented smartphone-based DDA with 48 problem drinkers aged 50 to 73 demonstrated that 100% had their own smartphones, and compliance rates with the DDA were higher among older adults than the younger cohort (78% vs. 72% over the course of 49 days) [56].…”
Section: Cellular Phones and Smartphonesmentioning
confidence: 99%
“…To test the feasibility of using an electronic diary, a review of studies using electronic diary-related pain or pain-related disability measurement was conducted, as well as the identification or development of an application or text system with candidate diary prompts and FEASIBILITY RANDOMISED CONTROLLED TRIAL NIHR Journals Library www.journalslibrary.nihr.ac.uk choice of prompts and frequency. 117 Research participants find electronic symptom diaries acceptable and can generate valid symptom data. 118 During the exploratory phase, initial feasibility testing, we refined the diary recording for the needs of the trial.…”
Section: Primary Outcomementioning
confidence: 99%